Comparison of mortality rates in solid vs hematological cancer patients post COVID-19 treatment at Dr. Soetomo General Hospital, Surabaya (2020–2021) - Hamdani, Muhamad Husni Thamrin; Joni, Wahyuhadi,; Indarto, Susilo, Rahadian; Budi, Utomo, (Edelweiss Applied Science and Technology, 2025)
The COVID-19 pandemic significantly impacted cancer patients due to their immunocompromised status and comorbid conditions. However, comparative data on mortality outcomes between solid and hematological cancer patients post-COVID-19 treatment remains limited. This study aimed to analyze the mortality differences in these groups at Dr. Soetomo General Hospital, Surabaya, between 2020 and 2021. A retrospective cohort analysis was conducted using patient medical records. Inclusion criteria covered cancer patients confirmed with COVID-19 who underwent treatment and had complete mortality outcome data. Variables included cancer type, comorbidities, gender, and mortality. Statistical analysis involved chi-square tests and multivariate logistic regression. Among 237 patients, 78% had solid tumors, and 74.7% had comorbidities. No statistically significant difference in mortality was observed between cancer types (p > 0.05). However, comorbidities significantly influenced mortality risk (p < 0.001; RR = 25.08; 95% CI: 3.56–176.55). Comorbidities are a major determinant of mortality among cancer patients recovering from COVID-19, regardless of cancer type. Addressing comorbid conditions aggressively may reduce fatal outcomes in this vulnerable population.